Critical Dimensions in Architectural Photography: Contributions to Architectural Knowledge. (February 2017) - Christenson, Mike
Abstract : This paper illustrates and explores three critical dimensions of photography in architecture, each of which informs the production of images, texts, and other artifacts which establish what might be called a building's media footprint . The paper's broad goal is to question the extent to which these critical dimensions are relevant to architectural decision-making processes. Acknowledging that such dimensions as the ones examined here rarely predict an architect's specific design decisions in a transparent manner, the paper discusses not only the decisions made by architects during the process of designing buildings, but the decisions made by critics, visitors, and members of the general public as they engage in activities such as visiting buildings, writing about them and, particularly, photographing them. First, the text discusses the potential of buildings to operate as mechanisms for producing images, in the sense originated by Beatriz Colomina. The question is developed through the analysis of the space of photography – mapping of points of view, directions of view, and fields of view of defined photographic collections. Secondly, it considers photography's complicity in the canonization of buildings, and specifically, the extent to which photography is responsible for distinguishing between major and minor architectural works. Finally, the essay examines the erosion over time of photography's historical power to frame when confronted with contemporary technologies of virtual reality and photorealistically rendered digital models. Each of these critical dimensions, or concepts, develops a specific aspect of how photographic information about buildings is organized, structured, and disseminated, and is thus only part of the larger project of architectural epistemology, which inquires into this wider field. This will be done through an examination of the Mies van der Rohe-designed Commons Building at ITT in Chicago and the evolution of its relationship with architectural photography and photographic representation – both on its own terms and through the prism of the Rem Koolhaas-designed McCormick Tribune Student Center, which adds to and incorporates the Commons Building. Until the end of the twentieth century, the Commons Building on the campus of the Illinois Institute of Technology was generally considered one of Mies van der Rohe's lesser works. Reportedly neglected by its own architect during the design process, and frequently marginalized in academic discussions of the campus, when mentioned at all the building was often cited as an unrefined prototype of Crown Hall. This discourse took a new direction when in 1998, Rem Koolhaas/OMA won a design competition for a student center on the IIT campus: uniquely among the competition entries, Koolhaas's design incorporated the Commons Building within a new context – what ultimately became the McCormick Tribune Campus Center (MTCC). When critics concluded that the incorporation of the Commons Building into the larger whole could compromise its integrity as an exemplar of Mies's work, the building became the object of renewed interest and controversy. The two projects considered here show a clear evolution in architecture's relationship with the photographic image. Specifically, the history of the Commons Building can be traced through photographs: during and shortly following its construction, the building was photographed as part of Mies's own attention to publicity; it was documented as part of historical analyses; and over time it was visited and photographed by casual and amateur photographers. Following the competition results, photographs of the Commons Building were strategically deployed by both proponents and critics of Koolhaas's design. Contemporary photographs of the building appear in architectural and campus guidebooks and on websites such as Flickr.com . Examining the ways in which photographs of the Commons Building appear in these various contexts allows discussion of the critical dimensions identified above and permits us to trace the evolution of the mutually reinforcing relationship between architecture and photography.